2018
DOI: 10.17977/um003v4i32018p108
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Style and Interpersonal Communication of Employee Satisfaction and It’s Effect on the Employee Performance

Abstract: This study aims to determine the relationship between leadership style, interpersonal communication to employee job satisfaction and its effect on employee performance. The method used in this study is path analysis with SPSS application version 21. These results indicate that the relationship of leadership style on employee job satisfaction has a contribution of 0.24, while the relationship between leadership style on the performance of employees have a contribution of 0.279. In addition, the relationship bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
(29 reference statements)
1
1
0
Order By: Relevance
“…This result also in line with other studies which stated that job satisfaction does not influence the job performance of service workers on McConnell Dowell Services Company (Parlaungan and Ramadhan, 2019). Similar research results were also found by Kulachai et al, (2018), Putri (2018), and Husein and Hanifah (2019) who stated that job satisfaction did not significantly influence job performance.…”
Section: Jobsupporting
confidence: 91%
“…This result also in line with other studies which stated that job satisfaction does not influence the job performance of service workers on McConnell Dowell Services Company (Parlaungan and Ramadhan, 2019). Similar research results were also found by Kulachai et al, (2018), Putri (2018), and Husein and Hanifah (2019) who stated that job satisfaction did not significantly influence job performance.…”
Section: Jobsupporting
confidence: 91%
“…For example, the transformational "democratic" leadership style might enhance the job performance more than other styles such as transactional leadership. Moreover, according to a study conducted by Putri (2018) to figure out the relationship between leadership and some factors such as interpersonal communications, job satisfaction, performance and motivation, the researcher found a significant positive relationship between leadership styles and employees' motivation and performance which lead to higher productivity. Also, the researcher elaborated and recommended to adopt more than of style of leadership to satisfy most of the employees.…”
Section: Leadership Stylementioning
confidence: 99%
“…Researchers claim that adopting the CHRL style in the light of interpersonal communication and leader vision is pivotal and very much needed to enhance the JP in organizations (AlKayid et al, 2023;Edgar et al, 2021;Le Blanc et al, 2021;Putri, 2018). Most of the studies suggested that the charismatic leadership style positive impact on job performance (Kirkpatrick & Locke, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to increase the job performance. On the other hand, if leaders communicate in a vague, confusing, or uninspiring way, they are less likely to be effective (Putri, 2018;Singh, 2014). Therefore, the quality of interpersonal communication can also affect the way that followers perceive the leader's charisma (Men et al, 2021).…”
Section: Interpersonal Communication As a Mediatormentioning
confidence: 99%
See 1 more Smart Citation